Human health benefits of plant bioactive compounds : potentials and prospects - Goyal, Megh Raj; Suleria, Hafiz (Palm Bay, Florida : Apple Academic Press, 2019)
"Human Health Benefits of Plant Bioactive Compounds: Potentials and Prospects focuses on the importance of functional foods and their secondary metabolites for human health, presenting new insights with scientific evidence on the use of functional foods in the treatment of certain diseases. The plants covered and their bioactive compounds are easily accessible and are believed to be effective with fewer side effects in comparison with modern drugs in the treatment of different diseases. They contain chemical compounds that can modify and modulate biological systems, eliciting therapeutic effects. Some plants and derived products mentioned include black carrot, olive oil, citrus peel, grapes, candy leaf, cereals and grains, and green and black tea. The volume is divided into four sections that cover these topics: Functional foods for human health, which discusses the concept of functional foods, the available sources, biochemistry, structural composition, and different biological activities, especially antioxidant activity. It also highlights the importance of functional foods and their health perspectives. Pharmacological aspects of fruits and vegetables, which focuses on the extraction of bioactive molecules, phytochemistry, and biological activities of a selection of plants. Pharmacological aspects of natural products, which explores bioactive compounds, structural attributes, bioactivity of anthocyanin, piceatannol, and a review of the ethnobotany/and medicinal properties of green and black tea. Pharmacological aspects of cereals and grains, which reviews the health benefits of flax seed, wheatgrass juice, and use and therapeutic potential as supplements for various disease management. This compendium sheds new light on the potential of functional foods for human health and contributes to the ocean of knowledge on food science and technology. It will be valuable for faculty, students, and researchers as well as those working in the food, nutraceuticals, and herbal industries."--
Includes index.
OCLC-licensed vendor bibliographic record.
Keywords: Plant bioactive compounds -- Health aspects; Functional foods; Botanical chemistry; HEALTH & FITNESS / Nutrition; SCIENCE / General; TECHNOLOGY / Food Science